Le journal retrouvé. Les spatialités d’un géographe normalien en 1893 - Pascal Clerc (Cybergeo, 2017)
In 1893, the future geographer Maurice Zimmermann was student at the École Normale Supérieure in Paris. During this year he hold his diary and carefully described his daily, his moods but also its spatial practices. Thus, it is possible to make a spatial biography of Zimmermann during this year in Paris: his favorite places, his movements and the territory that these practices can build. In addition, studying a diary is a way to understand the sensitive and emotional dimension of spatial practices.